Planning a site for new village or small town to safeguard the health of the population - Bekele, Damtew (Journal of Medicine and Health Sciences Research, 2023)
There is no doubt that health will help reduce the transmission of infectious agents. For the health of individuals, the prior elements to be fulfilled include the availability of pure water, keeping sanitation and hygiene are necessary for reducing infection of all sorts. To make these, change of habits by involving community participation in both urban and rural areas are inevitable to combat communicable diseases. It can be achieved also if initiations should be taken and participation held in both governmental and non-governmental organizations in issues related to the health of the nation. Furthermore, the creation of awareness of the prevailing problems is a prerequisite for any plan of action towards improving the situation.